Reduced ER–mitochondria connectivity promotes neuroblastoma multidrug resistance. (25th February 2022) - Çoku, Jorida; Booth, David M; Skoda, Jan; Pedrotty, Madison C; Vogel, Jennifer; Liu, Kangning; Vu, Annette; Carpenter, Erica L; Ye, Jamie C; Chen, Michelle A; Dunbar, Peter; Scadden, Elizabeth; et al.
Abstract: Most cancer deaths result from progression of therapy resistant disease, yet our understanding of this phenotype is limited. Cancer therapies generate stress signals that act upon mitochondria to initiate apoptosis. Mitochondria isolated from neuroblastoma cells were exposed to tBid or Bim, death effectors activated by therapeutic stress. Multidrug‐resistant tumor cells obtained from children at relapse had markedly attenuated Bak and Bax oligomerization and cytochrome c release (surrogates for apoptotic commitment) in comparison with patient‐matched tumor cells obtained at diagnosis. Electron microscopy identified reduced ER–mitochondria‐associated membranes (MAMs; ER–mitochondria contacts, ERMCs) in therapy‐resistant cells, and genetically or biochemically reducing MAMs in therapy‐sensitive tumors phenocopied resistance. MAMs serve as platforms to transfer Ca 2+ and bioactive lipids to mitochondria. Reduced Ca 2+ transfer was found in some but not all resistant cells, and inhibiting transfer did not attenuate apoptotic signaling. In contrast, reduced ceramide synthesis and transfer was common to resistant cells and its inhibition induced stress resistance. We identify ER–mitochondria‐associated membranes as physiologic regulators of apoptosis via ceramide transfer and uncover a previously unrecognized mechanism for cancer multidrug resistance. Synopsis: Longitudinal analysis of patient‐derived tumor cell lines identifies reduced levels of ER–mitochondria‐associated membranes (MAMs; ER–mitochondria contacts, ERMCs) as a novel contributor to multidrug resistance in childhood neuroblastoma. Mitochondria from drug‐resistant neuroblastoma cells exhibit attenuated apoptotic signal transduction, cytochrome c release, and MAMs. Transfer of Ca 2+ from MAMs to mitochondria is not required for reduced apoptosis in therapy‐resistant cells. Disruption of ceramide biosynthesis at MAMs and of lipid transfer to the outer mitochondrial membrane decreases apoptotic signaling and enhances multidrug resistance in relapsed cells. Abstract : Impaired ceramide biosynthesis at ER–mitochondria‐associated membranes and lipid transfer into mitochondria decreases apoptotic signaling in relapsed tumor cells, contributing to cancer therapy resistance.